WACANA TAKWIM URFI DALAM PENANGGALAN ISLAM - Jayusmman (Jurnal Hukum Islam, 2009)
As a calendar that uses an average calculation, Urfi calendar (takwim Urfi) is based on Urfi computation. It is agreed by scholars, that the use of takwim Urfi as a guidance in the performing of religious obligations is not valid. But because of the ease and regularity calendar computations based on Urfi reckoning, it can be used as alternatives in the discourse of international unification of Hijri calendar in Islam.